Intermediate-term neurodevelopmental outcomes and quality of life after arterial switch operation beyond early neonatal period. (21st June 2021) - Ramanan, Sowmya; Sundaram, Soumya; Gopalakrishnan, Arun; Anija, D V; Sandhya, P; Jose, Dhiya Susan; Baruah, Sudip Dutta; Menon, Sabarinath; Dharan, Baiju S
Abstract: : OBJECTIVES: The study objective was to evaluate the cardiac, neurodevelopmental, psycho-social and health-related quality of life (HRQOL) outcomes of children who underwent an arterial switch operation (ASO). METHODS: Children who underwent ASO were evaluated on follow-up at 3–5 years with cardiovascular, neurodevelopmental and HRQOL assessment using validated tools. Children with developmental delay, attention-deficit hyperactivity disorder, autism spectrum disorder, neuromotor and speech and language impairment were considered to have neurodevelopmental disorder (NDD). The impact of socioeconomic status (Kuppuswamy classification), perioperative cardiac, nutritional and psycho-social factors on outcomes was analysed. RESULTS: There were 61 (89.7%) survivors at a mean follow-up of 50.9 ± 7.6 months. The median age at surgery was 41 days (22–74.5). One-third of patients had growth restriction. Two children had residual cardiovascular lesions requiring intervention. The mean HRQOL score was >90 in all scales of the Paediatric Quality of Life Inventory™ 3.0 Cardiac Module. Neurological abnormalities were seen in 19 patients (31.1%) of whom 17 (27.9%) patients had NDD and 12 had developmental delay. Speech and language impairment, attention-deficit hyperactivity disorder, and neuromotor impairment were found in 16.4%, 3.3% and 6.7% patients, respectively. On multivariate analysis, increasing time to lactate normalization and low socioeconomic status were associated with developmental delay after ASO. CONCLUSIONS: While intermediate-term cardiac outcomes and HRQOL after ASO were fairly satisfactory, NDD was identified in one-fourth of these children. Increasing time to lactate normalization after ASO and low socioeconomic status were associated with suboptimal intermediate neurodevelopment outcomes after ASO. Abstract : Advances in surgical techniques and perioperative care have significantly lowered the mortality rates for children and adolescents with complex congenital heart disease (CHD) over the past several decades.